The Impact of Digital Payments on Financial Inclusion in Rural Areas - Yuko, Mohammad; Suratin, Mochammad; Mahfudz; Sukresna, I Made (LifeSciFi, 2025)
In the modern digital era, achieving financial inclusion remains a significant challenge, particularly in rural areas of Indonesia, where access to financial services is still limited. With only 70.13% of the rural population financially included, a substantial portion of individuals continue to rely on the informal financial sector, which often fails to meet their financial needs effectively. In response to these challenges, digital payment technology has emerged as a viable solution to bridge the gap in financial access. This study investigates the impact of digital payments on financial inclusion in rural East Java, employing a quantitative survey approach through questionnaires administered to digital payment users. The findings reveal that the adoption of e-wallets and QR payments significantly enhances community access to financial products and services. These results offer valuable insights for policymakers and stakeholders in formulating more effective strategies to improve financial inclusion in rural areas, thereby fostering economic growth and enhancing the overall well-being of communities.